Otherwise we make this a sea of photovoltaic panels": (Re)enacting energy modernity in Portuguese rural landscapes? Some reflections from Castelo de Vide and Graciosa - Batel, S.; Alba, M.; Valquaresma, A. (2nd International Congress of Ecological Humanities, 2025)
In the last decades, rural areas have been centerstage of a critical energy social sciences’ research agenda, as the local resistance to the injustices of the renewable energy transition has increased. At the same time, far-right populism and related modernist rhetoric has been on the rise across the world. However, the relations between far-right populism, its nationalist rhetoric, and the renewable energy transition as experienced by rural communities have not often been examined. This paper aims to contribute to this area of research by exploring, based on interviews, how two rural communities in Portugal – Graciosa in the Azores islands and Castelo de Vide in mainland Portugal – where votes for the far-right populist Portuguese party have increased in the last elections and where large-scale renewable energy infrastructures have been deployed or are planned, experience and make sense of these issues and relations between them. It will particularly explore how these relations are shaped by (dis)continuities between the energy ‘high-modernist’ period that has shaped Portuguese rural landscapes, namely during the dictatorship (1926–1974) and materialized in rural areas through large-scale hydroelectric dams and associated infrastructures; and the aesthetics of the current renewable energy transition and the cultural and moral landscapes it enacts.